A Bay of Blood - Bava, Mario; Auger, Claudine; Pistilli, Luigi; Camaso, Claudio (Arrow Films, 2010)
Countess Federica, the elderly owner of a coveted piece of bayside property, is brutally slain by her husband - who is himself killed by a mysterious third person at the murder scene! Who is the killer? Could it be the real estate developer or the entomologist neighbor who wants to preserve the natural insect life thriving around the bay? Perhaps the Countess's illegitimate son, in a bid to claim a name for himself, is responsible? Whoever it is, brace yourself, because no one's a suspect for very long in Mario Bava's black comedy of human greed - which boasts 13 characters and 13 of the most shocking murders ever filmed! [www.play.com]